Evaluation of color matching of single-shade resin composite to natural teeth using instrumental and visual techniques - Tayyem, Lina A.; Sawair, Faleh A.; Hamdan, Ahmad A.; Jamani, Kifah D.; Hattar, Susan (International Journal of Innovative Research and Scientific Studies, 2025)
To investigate the blending capacity of a supra-nano filled resin composite with the surrounding natural tooth structure, sixty extracted teeth were randomly divided into two groups. Standardized class V cavities were restored with two types of resin composites: single-shade Omnichroma (experimental group-OMN) and multi-shade Estelite Σ Quick (control group-MS). Teeth were evaluated instrumentally using the Vita Easyshade spectrophotometer, and calculations of color difference CIELAB and CIEDE2000 were performed. Visual assessment was conducted by six calibrated observers using a defined Likert scale from 0 to 4. Significant differences between the MS and OMN groups were noted for different color parameters. The color difference △Eab for the OMN group (14.37) was significantly higher than that of the MS group (10.04) with a p-value < 0.05. Analysis of the overall color difference △E00 revealed no significant difference between the OMN group (△E00=9.85) compared to the MS group (△E00=7.85). In visual assessment, the overall median reading for the MS group was 0.5 compared to 0.92 for the OMN group, with a p-value of 0.01. However, both values were located within the 0-1 category. The supra-nano resin composite (Omnichroma) showed a higher color difference value compared to the multi-shade composite when tested on natural teeth. Nevertheless, the visual results for both composites were within clinically acceptable levels. The single-shade resin composite might be considered a valuable substitute to simplify the restorative procedure in less demanding esthetic clinical situations.